ANTIBACTERIAL ACTIVITY OF MIANA LEAF ESTRACT (Coleus atropurpereus) ON Steptococcus aureus - Anita, Anita; Basarang, Mujahidah; Rahmawati, Rahmawati (Media Kesehatan Politeknik Kesehatan Makassar, 2020)
ABSTRACTMiana leaf(Coleus atrropurpureus) is the one of biofarmacology plant which using for antibacterial activity.Miana leaf contains flavonoid, tanin, saponin  which can inhibit growth of bacteria. The aims this research were study antibacterial activity of miana leaf extract on Streptococcus aureus.This research used laboratory observation method which used miana leaf extract concentration 250 mg/ml, 125 mg/ml,  62.5 mg/ml, 31,25 mg/ml, and 15,625 mg/ml. This research used tetracylin for positive control and aquadest for negative control which growth 0n 37o C  used difusion agar method. The results showed antibactrila activity  miana leaf  extract with a concentration 250 mg/ml with inhibition zone 0.00 mm, 125 mg/ml with inhibition zone 0,00 mm, 62,5 mg/ml with inhibition zone 0,00 mm, 31,25 mg/ml with inhibition zone 0,00 mm, and 15,62 mg/ml with inhibition zone 0,00 mm. For positive control showed inhibition zone 27,6 mm and negative control with inhibition zone 0,00 mm. Miana leaf extract concentration 250 mg/ml, 125 mg/ml, 62,5 mg/ml, 31,25 mg/ml and 15,62 mg/ml were not effectively inhibit Streptococcus sp.